2022
DOI: 10.3389/fenvs.2022.845147
|View full text |Cite
|
Sign up to set email alerts
|

Consequences and Drivers of Differentiated Environmental Regulation Policies on Hog Production in China: A Spatial Econometrics Approach

Abstract: Using a spatial econometric approach and national prefecture-level hog inventory data, this paper analyzes the extent to which environmental regulation policies influence hog production in China, and obtained the following research results: 1) During the 12th Five-Year Plan period, environmental regulation policies will significantly reduce the output of the hog industry in highly regulated areas. 2) The specific policy commands from the central government targeting on livestock sector and a high share of agri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 56 publications
0
5
0
Order By: Relevance
“…Hog production. In this study, we followed the approach of previous studies [5,6] in using the number of stocked heads as an indicator of hog production. Specifically, we used the natural logarithm of yearend hog stock in each county as the outcome measure.…”
Section: Data Descriptionmentioning
confidence: 99%
See 3 more Smart Citations
“…Hog production. In this study, we followed the approach of previous studies [5,6] in using the number of stocked heads as an indicator of hog production. Specifically, we used the natural logarithm of yearend hog stock in each county as the outcome measure.…”
Section: Data Descriptionmentioning
confidence: 99%
“…Existing studies have shown that environmental regulations can negatively impact hog production, leading to a reduction in the number of hogs slaughtered, live hog inventory, and pork production by 8.3%, 10.3%, and 11.2%, respectively [5]. Zeng et al (2022) [6] used a spatial econometric approach to show that these regulations significantly impact the hog industry in highly regulated areas. These studies evaluating hog-relocation policies and regulations have consistently shown that such regulations lead to reduced animal numbers rather than the relocation of production capacity [5,6].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Existing studies have shown that environmental regulations hurt hog production because they reduce the number of hogs slaughtered, the inventory of live hogs, and pork production by 8.3%, 10.3%, and 11.2%, respectively (Chen et al, 2021). Zeng et al (2022) use a spatial econometric approach and national prefecture-level hog inventory data to show that environmental regulation policies signi cantly reduce the output of the hog industry in highly regulated areas. Some studies offer a systematic evaluation of the effectiveness of the hog-relocation policies and regulations in curbing production and improving water quality ( Chen et al, 2021;Cheng et al, 2022).…”
Section: Introductionmentioning
confidence: 99%